Population genetics of the bigeye thresher shark Alopias superciliosus in the Atlantic and Indian Oceans: implications for conservation - Morales, Millke Jasmine Arminini [UNESP]; Mendonça, Fernando Fernandes; Magalhães, Carolina Oliveira [UNESP]; Oliveira, Claudio [UNESP]; Coelho, Rui; Santos, Miguel Neves; Cruz, Vanessa Paes [UNESP]; Piercy, Andrew; Burgess, George; Hazin, Fabio Vieira; Foresti, Fausto [UNESP] (Springer Nature, 2018)
Population structure and genetic connectivity are pivotal contributions to the establishment of conservation strategies for fisheries management, in particular for highly migratory species that are affected by commercial fisheries. This study used partial sequences of mitochondrial DNA control region to determine the genetic structure of the bigeye thresher shark Alopias superciliosus in the Atlantic and Indian Oceans. A total of 858 base pairs of mtDNA CR from 228 individuals were analyzed. The resulting nucleotide diversity (π) was 0.0011 ± 0.0008 and the haplotype diversity (h) was 0.127 ± 0.030. These are the lowest diversities registered in elasmobranchs with this genetic marker. Two genetically distinct lineages were identified, one of them represented by 3.9% of the analyzed individuals and none restricted to any particular area. Simulated scenarios of population structure, tested with AMOVA and pairwise ΦST did not result in significant values indicating high connectivity among all sampled groups. The absence of population structure, even between Atlantic and Indian Oceans, corroborates the high dispersal ability of this species. The low genetic diversity detected in this species and the identification of two historical lineages occurring in sympatry, one represented by a very small number of individuals, should be considered in the conservation efforts and management plans of A. superciliosus.
Keywords: Alopiidae; Conservation genetics; Fisheries management; Mitochondrial DNA; Population genetics